Amendment 19 women's right to vote - Fabian, Rhonda; Baber, Jerry; Cambridge Educational (Monmouth Junction, N.J. : Cambridge Educational, 2004)
This program explores the history and implications of the nineteenth amendment
Title from cover
Adapted from Amendments to the Constitution : a brief legislative history
Executive producer, Edward T. Gardner ; camera, Mark Dombrow ; editors, Jonathan M. Danley, Ron Schindlinger ; writers, Aaron Myers, Jack Phelan, Rhonda Fabian
Narrator : Gene Shay
DVD format
Keywords: United States; Constitutional amendments -- United States; Voting -- United States; Suffrage -- United States; Woman -- Suffrage -- United States